2009
DOI: 10.1037/a0016648
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the effects of argument length and validity on inductive and deductive reasoning.

Abstract: In an effort to assess models of inductive reasoning and deductive reasoning, the authors, in 3 experiments, examined the effects of argument length and logical validity on evaluation of arguments. In Experiments 1a and 1b, participants were given either induction or deduction instructions for a common set of stimuli. Two distinct effects were observed: Induction judgments were more affected by argument length, and deduction judgments were more affected by validity. In Experiment 2, fluency was manipulated by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
112
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 54 publications
(124 citation statements)
references
References 56 publications
(77 reference statements)
11
112
1
Order By: Relevance
“…In terms of the signal detection account illustrated in Figure 3B, the analytic system may act to determine the position of arguments along the axis of argument strength, while the heuristic system might use knowledge-based cues such as believability to determine the location of the response criterion. Furthermore, our data do not rule out alternative, more complex, signal detection interpretations of dual process theory (e.g., the multidimensional account in Heit & Rotello, 2008, in press;Rotello & Heit, 2009), but these are not required to account for the data from Experiments 1-3.…”
Section: Discussionmentioning
confidence: 88%
See 4 more Smart Citations
“…In terms of the signal detection account illustrated in Figure 3B, the analytic system may act to determine the position of arguments along the axis of argument strength, while the heuristic system might use knowledge-based cues such as believability to determine the location of the response criterion. Furthermore, our data do not rule out alternative, more complex, signal detection interpretations of dual process theory (e.g., the multidimensional account in Heit & Rotello, 2008, in press;Rotello & Heit, 2009), but these are not required to account for the data from Experiments 1-3.…”
Section: Discussionmentioning
confidence: 88%
“…Second, in a series of simulations comparing A z and d a , Macmillan et al (2004) showed that A z is a relatively unbiased measure of accuracy and has a smaller standard error than d a . Our experiments provide the first ROC data in the syllogistic reasoning task, but ROCs from other reasoning tasks have been curvilinear and asymmetric (Heit & Rotello, 2005Rotello & Heit, 2009). Those data suggest two key points: (a) The use of H Ϫ F as a measure of reasoning performance in the belief bias task is probably inappropriate, and (b) application of dЈ would confound sensitivity with response bias.…”
Section: A Signal Detection Model Of Syllogistic Reasoningmentioning
confidence: 95%
See 3 more Smart Citations